2021
DOI: 10.1177/0022219420988001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computerized Versus Collaborative Professional Development on Teachers’ and Students’ Performance Related to the Concept Anchoring Routine

Abstract: Two studies investigated the effects of a live, collaborative Professional Development (PD) program versus individualized PD with a multimedia software program. For both studies, teachers were randomly assigned to either a Virtual Workshop (VW) group that used the software program or to an Actual Workshop (AW) group that participated in a face-to-face workshop that included collaborative activities. The same teaching routine, the Concept Anchoring Routine, was taught to the teachers in both studies. In Study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In both studies, the effect sizes were large. Indeed, in three studies (Schumaker et al., 2010; Schumaker et al., 2021a, 2021b), more teachers who experienced the computerized instruction produced implementation performances above the 80% mastery level than the teachers who experienced live instruction. Additionally, Schumaker et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In both studies, the effect sizes were large. Indeed, in three studies (Schumaker et al., 2010; Schumaker et al., 2021a, 2021b), more teachers who experienced the computerized instruction produced implementation performances above the 80% mastery level than the teachers who experienced live instruction. Additionally, Schumaker et al.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the effect sizes were large. Indeed, in three studies (Schumaker et al, 2010;Schumaker et al, 2021aSchumaker et al, , 2021b, more teachers who experienced the computerized instruction produced implementation performances above the 80% mastery level than the teachers who experienced live instruction. Additionally, Schumaker et al (2010) and Schumaker et al (2021a) found that the whole group of students of the VW teachers earned significantly higher scores than the whole group of students of the AW teachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations